Through Jewish Eyes: Polemical Literature and the Medieval Papacy. Issue 333 (December 2013) - Rist, Rebecca
Abstract Although the medieval papacy's stance towards the Jews is a well‐established area of research, Jewish ideas about the papacy remain a surprisingly underdeveloped historical topic. This article explores such ideas through the genre of polemic and disputational literature. Jewish writers were keen to ensure the safety of their communities in western Europe and grateful for statements of papal protection. They fully acknowledged that popes had always played and would continue to play an important role in safeguarding their well‐being and determining their future. Yet although contemporary and later writers often valued papal protection more highly than that of monarchs, emperors or clergy, they also knew that it had its carefully circumscribed limits. Furthermore, although they were respectful of the papacy's power, both spiritual and temporal, they were dismissive of the scriptural and theological formulations on which Christian claims for apostolic authority rested and highly critical of Christian beliefs about the papacy, in particular that of apostolic succession. Jewish ideas about both individual popes and the medieval papacy as an institution are therefore nuanced and complex; they deserve rigorous and wide‐ranging investigation and it is hoped that this article will contribute to their better understanding.